Discovery and Preliminary Characterization of a Third Interstellar Object: 3I/ATLAS - Darryl Z. Seligman; Marco Micheli; Davide Farnocchia; Larry Denneau; John W. Noonan; Henry H. Hsieh; Toni Santana-Ros; John Tonry; Katie Auchettl; Luca Conversi; Maxime Devogèle; Laura Faggioli; et al. (The Astrophysical Journal Letters)
We report initial observations aimed at the characterization of a third interstellar object. This object, 3I/ATLAS or C/2025 N1 (ATLAS), was discovered on 2025 July 1 UT and has an orbital eccentricity of e  ∼ 6.1, perihelion of q  ∼ 1.36 au, inclination of ∼175°, and hyperbolic velocity of V _∞  ∼ 58 km s ^−1 . We report deep stacked images obtained using the Canada–France–Hawaii Telescope and the Very Large Telescope that resolve a compact coma. Using images obtained from several smaller ground-based telescopes, we find minimal light-curve variation for the object over a ∼4 day time span. The visible/near-infrared spectral slope of the object is 17.1% ± 0.2%/100 nm, comparable to other interstellar objects and primitive solar system small bodies (comets and D-type asteroids). Moreover, 3I/ATLAS will be observable through early 2025 September, then unobservable by Earth-based observatories near perihelion due to low solar elongation. It will be observable again from the ground in late 2025 November. Although this limitation unfortunately prohibits detailed Earth-based observations at perihelion when the activity of 3I/ATLAS is likely to peak, spacecraft at Mars could be used to make valuable observations at this time.